Respuesta :

Assignment: [tex]\bold{Simplify \ Expression: \ 80g+30h=10\left(g+h\right)}[/tex]

<><><><><><><>

Answer: [tex]\boxed{\bold{g=-\frac{2h}{7}}}[/tex]

<><><><><><><>

Explanation: [tex]\downarrow\downarrow\downarrow[/tex]

<><><><><><><>

[ Step One ] Expand [tex]\bold{10\left(g+h\right): \ 10g+10h}[/tex]

[tex]\bold{80g+30h=10g+10h}[/tex]

[ Step Two ] Subtract 30h From Both Sides

[tex]\bold{80g+30h-30h=10g+10h-30h}[/tex]

[ Step Three ] Simplify

[tex]\bold{80g=10g-20h}[/tex]

[ Step Four ] Subtract 10g From Both Sides

[tex]\bold{80g-10g=10g-20h-10g}[/tex]

[ Step Five ] Simplify

[tex]\bold{70g=-20h}[/tex]

[ Step Six ] Divide Both Sides By 70

[tex]\bold{\frac{70g}{70}=\frac{-20h}{70}}[/tex]

[ Step Seven ] Simplify

[tex]\bold{g=-\frac{2h}{7}}[/tex]

<><><><><><><>

[tex]\bold{\rightarrow Mordancy \leftarrow}[/tex]

S1NGH

Answer:

[tex]g= -\frac{7}{2}[/tex]

Step-by-step explanation:

80g + 30h = 10g + 10h

70g = -20h

g = [tex]-\frac{70}{20} = -\frac{7}{2}[/tex]